(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
The need for precise age estimation techniques has grown in recent years because of the increased number of unidentified humans remains, unidentified corpses, and situations where there is no real record of birth. Almost every stage of life is affected by medico-legal issues involving age estimation. To identify ossification and fusion activities relevant for estimation of specific age groups of medico legal importance the present study was conducted in the department of Forensic medicine and toxicology, M.L.N. Medical College, Prayagraj which comprised of the 391 skiagrams (120 for knee joint and 271 for pelvis) aged 14 years to 24 years who attended the department of Radiology, S.R.N. Hospital, M.L.N. Medical College, Prayagraj, Uttar Pradesh during the study period for various radiological examinations.